2003
DOI: 10.1088/0953-4075/36/13/316
|View full text |Cite
|
Sign up to set email alerts
|

Dipole moment functions of iodine E0g –A1uand E0g –B  1utransitions

Abstract: The electric dipole moment functions of iodine E0g+–A1 u and E0g+–B′′1 u transitions in the range of 3.2–4.2 Å have been determined for the first time by simulating the luminescence spectra from the E0g+,v E = 9, JE ≈ 55 rovibrational level and the measured ratios of the total intensities of the E0g+–A1 u, E0g+–B′′1 u and E0g+–B0 u+ transitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…As in the case of v E ¼ 0 excitation, CINAT was observed only to D 0 þ u state. 65,67,76 As shown in Fig. 2, the total rate constant for the E !…”
Section: Electronic Structure Of Ip Statesmentioning
confidence: 87%
See 1 more Smart Citation
“…As in the case of v E ¼ 0 excitation, CINAT was observed only to D 0 þ u state. 65,67,76 As shown in Fig. 2, the total rate constant for the E !…”
Section: Electronic Structure Of Ip Statesmentioning
confidence: 87%
“…The experimental techniques used at Swarthmore and St. Petersburg to investigate the CINAT dynamics of I 2 (E) are similar (see details in refs. [65][66][67][68][69][70][71][72]76,77). Single rovibrational levels of the E 0 þ g state were populated through an OODR excitation scheme:…”
Section: Experimental and Theoretical Background 21 Experimental Tecmentioning
confidence: 99%
“…The calculated spectra had an estimated wavelength accuracy of ±0.01 Å and agreed well with the literature data. 25 The spectroscopic constants and/or potential curves from the following sources: X state, 26 B, 27 D, 28 a 0 + g , 24,28 A1 u , B 1 u , 29 were used for the experimental data analysis. Dipole moment functions for the D-X and E-B transitions were taken from Ref.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, one would believe that its intensity is much lower than that of the one-electron high frequency D → X transition. The D → X spectra are overlapped with the E-A and E-B , 29 and we simulated the D → X spectra to determine their total intensity.…”
Section: Methodsmentioning
confidence: 99%
“…C1 u (aa) emission. Subsequently, Akopyan et al [19] showed by simulation that the E0 þ g ð 3 P 2 Þðv ¼ 9Þ ! C1 u (aa) emission has a red extremum at 350 nm.…”
Section: General Implications For Other Collisional Energy Transfer Ementioning
confidence: 99%